Structure and dynamics of the yeast SWR1:nucleosome complex - Willhoft,O; Ghoneim,M; Lin,C-L; Chua,E; Wilkinson,M; Chaban,Y; Ayala,R; McCormack,E; Ocloo,L; Rueda,D; Wigley,DB (Science, 2018)
INTRODUCTIONCanonical nucleosomes contain two copies of each of four histone proteins: H2A, H2B, H3, and H4. However, variants of these histones can be inserted by adenosine triphosphate (ATP)–dependent chromatin-remodeling machines. The yeast SWR1 chromatin-remodeling complex, a member of the INO80 remodeler family, catalyzes the exchange of H2A-H2B dimers for dimers containing Htz1 (H2A.Z in human) in an ATP-dependent manner. However, the mechanism by which SWR1 exchanges histones is poorly understood. Despite having a DNA translocase subunit similar to that in the INO80 complex that slides nucleosomes, no net translocation of nucleosomes has been reported for SWR1. Consequently, the function of the ATPase activity, which is required for histone exchange in SWR1, has remained enigmatic.RATIONALETo obtain sufficient quantities for structural analysis, we generated the complete 14-subunit yeast SWR1 complex in insect cells. Binding of nucleosomes to SWR1 is stabilized in the presence of an ATP analog (ADP•BeF3), which we used to prepare a complex with a canonical yeast H2A-containing nucleosome. Structural analysis was undertaken by cryo–electron microscopy (cryo-EM). We also used single-molecule FRET (smFRET) techniques to probe the dynamics of nucleosomes bound to SWR1. Fluorescent probes were positioned on the H2A histones and the end of the DNA to monitor changes in nucleosome dynamics upon binding of SWR1 and ATP (or ATP analogs).RESULTSWe determined the cryo-EM structure of the SWR1-nucleosome complex at 3.6-Å resolution. The architecture of the complex shows how the SWR1 complex is assembled around a heterohexameric core of the RuvBL1 and RuvBL2 subunits. The Swr1 motor subunit binds at superhelical location 2 (SHL2), a position it shares in common with other remodelers but not with its most closely related complex, INO80, which binds at SHL6-SHL7. Binding of ATP or ADP•BeF3 to the SWR1-nucleosome complex induces substantial unwrap